Ladies' Paradise Based on a Novel by Émile Zola - Thibaudeau, Gabriel; Zola, Emile (Cinema of Discovery: Julien Duvivier in the 1920s, 2021)
Made at the dawn of the sound era, this feature from director Julien Duvivier marked the filmmaker’s last silent work. An adaptation of Emile Zola’s 1883 novel of the same name, it stars Dita Parlo as Denise, an orphaned woman who relocates to the City of Lights. [mubi.com]